Apertochrysa Tjeder, 1966, a new senior synonym of Pseudomallada Tsukaguchi, 1995 (Neuroptera: Chrysopidae: Chrysopinae: Chrysopini) - Breitkreuz, Laura; Duelli, Peter; Oswald, John (Zootaxa, 2021)
Apertochrysa Tjeder, 1966, is identified as a new senior subjective synonym of the large, subcosmopolitan, green lacewing genus currently known under the name Pseudomallada Tsukaguchi, 1995. Apertochrysa is rediagnosed and the taxonomic consequences of the new synonymy are reviewed. New combinations are created in Apertochrysa for 165 species formerly placed in Pseudomallada and for two species formerly placed in Mallada; three species are transferred from Pseudomallada back to previously-established combinations in Apertochrysa; and 13 additional species are retained in Apertochrysa from previous placements. This brings the total number of Apertochrysa species to 183.